SYNAPTIC PLASTICITY AND MOTOR LEARNING (Fiep Bulletin - online, 2014)
The volume and ability of processing information by the human brain depends not on the number of neurons but on the number of synaptic connections between them. The neural networks in the brain develop during one’s lifetime. Their development is affected by genetic and environmental factors as well as by acquired experiences. The plasticity of the healthy brain refers to a re-organization of the cortex in response to learning and experience. The key sites responsible for the creation and decay of brain plasticity are synapses. A synapse constantly modifies its properties affecting the efficiency of neurotransmission. This unique ability of synapses is known as synaptic plasticity and is regarded as the cellular foundation of learning and memory. The number of synapses and dendrites of cortical neurons increases when motor learning occurs with a simultaneous influence of environmental stimuli. Considering the significance of synapses in the learning process it can be stated that memories and experiences are not stored in the brain matter but in the inter-matter spaces (Douglas Fields 2009). Training and experience  ugment the cortical representation of exercised motor functions (Kinalski 2008).
Keywords: engram; synaptic augmentation; long-term potentiation (LT P); metaplasticity